2020
DOI: 10.1089/cyber.2019.0773
|View full text |Cite
|
Sign up to set email alerts
|

Unique and Cumulative Effects of Intimate Partner Cybervictimization Types on Alcohol Use in Lesbian, Gay, and Bisexual Emerging Adults

Abstract: The use of modern technology has inadvertently created newer platforms for intimate partner victimization to take place. The present study investigated (i) whether psychological, sexual, and stalking intimate partner cybervictimization (cyber IPV) types were uniquely associated with alcohol use, and (ii) whether there were additive effect of cyber IPV types on alcohol use, after controlling for histories of childhood maltreatment types, face-to-face intimate partner victimization among lesbian, gay, and bisexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Overall, prior studies suggest that higher levels of prejudice and perceived experiences of discrimination are related to higher levels of physical health problems, such as sleep difficulties, headaches, strong aches, and pain (Denton et al, 2014). Studies also suggest that prolonged internalized stigma, microaggressions, and victimization experiences could be associated with alcohol and marijuana use (Trujillo et al, 2020;Villarreal et al, 2021). Additionally, stigma and LGBTQ+ identity disclosure have been associated with greater levels of depression among gay and bisexual men (Pachankis et al, 2019;Talley & Bettencourt, 2011).…”
Section: Minority Stress and Healthmentioning
confidence: 98%
“…Overall, prior studies suggest that higher levels of prejudice and perceived experiences of discrimination are related to higher levels of physical health problems, such as sleep difficulties, headaches, strong aches, and pain (Denton et al, 2014). Studies also suggest that prolonged internalized stigma, microaggressions, and victimization experiences could be associated with alcohol and marijuana use (Trujillo et al, 2020;Villarreal et al, 2021). Additionally, stigma and LGBTQ+ identity disclosure have been associated with greater levels of depression among gay and bisexual men (Pachankis et al, 2019;Talley & Bettencourt, 2011).…”
Section: Minority Stress and Healthmentioning
confidence: 98%
“…Thus, the present study aims to examine whether witnessing mother-to-father and father-to-mother parental violence during childhood increases the likelihood of perpetrating cyber IPV during adulthood, and if these associations are similar across Hispanic men and women. Since WPV and childhood maltreatment (abuse and neglect) often co-occur (e.g., Charak et al, 2018) as do face-to-face IPV and cyber IPV types (Trujillo et al, 2020; Watkins et al, 2018), their effects were controlled for in order to examine the unique associations between WPV and cyber IPV types.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have also found that LGBTQ+ spaces, social networking, and dating applications may represent an essential way to satisfy LGBTQ+ needs such as a sense of existing in a community, receive social approval, and the opportunity to explore different ways to practice their sexuality (Corriero & Tong, 2015; Zervoulis et al, 2020; Miller, 2015). Future studies focusing on IPV in LGBTQ+ emerging adults should include analyses of specific consequences and correlates of cyber IPV, since prior research suggests that cyber IPV could be potentially harmful, generating high levels of distress and consequences in victims, such as an increased consumption of alcohol and greater levels of depression (Cantu & Charak, 2022; Marganski & Melander, 2015; Trujillo et al, 2020). Moreover, stalking behaviors have been related to physical and sexual face-to-face IPV, severe injuries and even homicide; therefore, failure to recognize the potential dangers of cyber stalking and psychological aggressions may have detrimental consequences on LGBTQ+ victim’s mental health (Charak et al, 2019; Messinger et al, 2018; Sargent et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of information and communication technologies (e.g., smartphones and social media), cyberspace has become a popular venue for dating relationships and as a result cyberspace is a platform where IPV can transpire especially in adolescents and emerging adults (Cano-Gonzalez et al, 2022; Cantu & Charak, 2022; Marganski & Melander, 2015; Trujillo et al, 2020; Watkins et al, 2018). Notably emerging adulthood encompasses individuals in the age range from 18 to 29 years old, a developmental stage wherein individuals focus on acquiring new relationships and searching for greater levels of intimacy while simultaneously creating their own identity (Arnett, 2000).…”
mentioning
confidence: 99%